2022
DOI: 10.52166/edulitics.v7i1.3028
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Youtube Movie Clips in Teaching Listening: Lecturer Practice and Students’ Opinions

Abstract: The use of YouTube in language teaching is no longer considered a new idea. In this study, the researcher investigated the use of YouTube movie clips in teaching listening from a student’s response, specifically in English education class. The study aims at portraying and describing the nature of how the lecturer applies YouTube movie clips in teaching listening classes for university students. The data were collected from the lecturer through observation, interviews, and field notes. A total of 26 English Dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Students admitted that watching an English movie can give them new insight and knowledge about the linguistics aspects. Following the previous study, Burhanuddin et al (2020), the results are relevant because students watch an English movie to improve their vocabulary, grammar, pronunciation, and spelling; Hidayah (2022) found that using subtitles while watching a video or movie helps understand the meaning. The students admit that using subtitles is helpful for their learning process.…”
Section: Impacts Of Using An English Movie On Students' Listening Skillmentioning
confidence: 74%
See 1 more Smart Citation
“…Students admitted that watching an English movie can give them new insight and knowledge about the linguistics aspects. Following the previous study, Burhanuddin et al (2020), the results are relevant because students watch an English movie to improve their vocabulary, grammar, pronunciation, and spelling; Hidayah (2022) found that using subtitles while watching a video or movie helps understand the meaning. The students admit that using subtitles is helpful for their learning process.…”
Section: Impacts Of Using An English Movie On Students' Listening Skillmentioning
confidence: 74%
“…On the other hand, Hidayah (2022) mentioned that teachers can use YouTube alongside traditional movies for learning. YouTube offers a wealth of authentic materials for language learning, making it easier for teachers to find relevant content across various genres.…”
Section: The Use Of English Movies For Language Learning Mediamentioning
confidence: 99%